Assessment instruments and depression rates in people with spinal cord injury: a systematic review - Aline Ferreira Placeres; Regina Célia Fiorati (SciELO, 2018)
ABSTRACT Objective: To identify, describe, differentiate and qualify the instruments used to evaluate depression and also identify the percentage and average rates of depression in people with spinal cord injury. Method: This is a systematic review of the literature implementing a qualitative approach. SciELO, LILACS, PubMed and PsycINFO databases were consulted. Original articles were classified according to the variables (Spinal Cord Injury, Depression and Assessment instruments). The studies are presented according to the instruments in recent publications in the past 11 years. Results: Five evaluation instruments were found. PHQ-9, a screening instrument for diagnosing depression was used in most studies, with all being performed in the United States and having a higher impact factor and number of participants. Studies with PHQ-9 presented a total score of people who met the criteria for depression without grading by severity with an average of 17.6% ± 7.3%, while BDI presented 51.6% ± 15.1% and the HADS showed 37.5% ± 31% of people with some degree of depression. Conclusion: This study was important in identifying which instruments can be used to assess depression, the description of each, some of their differences, which ones are used in the best studies and o the depression rates in different parts of the world. It was also important to show how the PHQ-9 is an important instrument, but is limited to being used in the USA.